Prochlorococcus marinus responses to light and oxygen - Savoie, Mireille; Mattison, Aurora; Genge, Laurel; Nadeau, Julie; Śliwińska-Wilczewska, Sylwia; Berthold, Maximilian; Omar, Naaman M; Prášil, Ondřej; Cockshutt, Amanda M; Campbell, Douglas A (PloS one, 2024)
Prochlorococcus marinus, the smallest picocyanobacterium, comprises multiple clades occupying distinct niches, currently across tropical and sub-tropical oligotrophic ocean regions, including Oxygen Minimum Zones. Ocean warming may open growth-permissive temperatures in new, poleward photic regimes, along with expanded Oxygen Minimum Zones. We used ocean metaproteomic data on current Prochlorococcus marinus niches, to guide testing of Prochlorococcus marinus growth across a matrix of peak irradiances, photoperiods, spectral bands and dissolved oxygen. MED4 from Clade HLI requires greater than 4 h photoperiod, grows at 25 μmol O2 L-1 and above, and exploits high cumulative diel photon doses. MED4, however, relies upon an alternative oxidase to balance electron transport, which may exclude it from growth under our lowest, 2.5 μmol O2 L-1, condition. SS120 from clade LLII/III is restricted to low light under full 250 μmol O2 L-1, shows expanded light exploitation under 25 μmol O2 L-1, but is excluded from growth under 2.5 μmol O2 L-1. Intermediate oxygen suppresses the cost of PSII photoinactivation, and possibly the enzymatic production of H2O2 in SS120, which has limitations on genomic capacity for PSII and DNA repair. MIT9313 from Clade LLIV is restricted to low blue irradiance under 250 μmol O2 L-1, but exploits much higher irradiance under red light, or under lower O2 concentrations, conditions which slow photoinactivation of PSII and production of reactive oxygen species. In warming oceans, range expansions and competition among clades will be governed not only by light levels. Short photoperiods governed by latitude, temperate winters, and depth attenuation of light, will exclude clade HLI (including MED4) from some habitats. In contrast, clade LLII/III (including SS120), and particularly clade LLIV (including MIT9313), may exploit higher light niches nearer the surface, under expanding OMZ conditions, where low O2 relieves the stresses of oxidation stress and PSII photoinhibition.
Keywords: mořská voda; světlo; Photoperiod; fotoperioda; Prochlorococcus; Oxygen; kyslík; Light; Seawater